2013
DOI: 10.1038/nature12170
|View full text |Cite
|
Sign up to set email alerts
|

Negligible impact of rare autoimmune-locus coding-region variants on missing heritability

Abstract: Genome-wide association studies (GWAS) have identified common variants of modest-effect size at hundreds of loci for common autoimmune diseases; however, a substantial fraction of heritability remains unexplained, to which rare variants may contribute. To discover rare variants and test them for association with a phenotype, most studies re-sequence a small initial sample size and then genotype the discovered variants in a larger sample set. This approach fails to analyse a large fraction of the rare variants … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
136
1
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 181 publications
(145 citation statements)
references
References 30 publications
7
136
1
1
Order By: Relevance
“…A recent exome sequencing study in CeD, using extended families (in a linkage analysis) and with re-sequencing of GWAS candidate genes, did not find any rare alleles in coding regions associated to the disease [27]. A similar scenario was presented by Hunt et al, who, after re-sequencing the exons of 25 candidate genes in 41,911 individuals, only identified a nearly "common" non-synonymous variant with very modest effect (rs17849502, minor allele frequency (MAF) ¼ 0.049, OR ¼ 1.35) in the NCF2 gene [26]. With hindsight, this variant was also found to be present in the CeD Immunochip study by Trynka et al, but it had been removed from further analysis by their quality control criteria [7].…”
Section: Immunochip In Other Autoimmune Diseasesmentioning
confidence: 56%
See 1 more Smart Citation
“…A recent exome sequencing study in CeD, using extended families (in a linkage analysis) and with re-sequencing of GWAS candidate genes, did not find any rare alleles in coding regions associated to the disease [27]. A similar scenario was presented by Hunt et al, who, after re-sequencing the exons of 25 candidate genes in 41,911 individuals, only identified a nearly "common" non-synonymous variant with very modest effect (rs17849502, minor allele frequency (MAF) ¼ 0.049, OR ¼ 1.35) in the NCF2 gene [26]. With hindsight, this variant was also found to be present in the CeD Immunochip study by Trynka et al, but it had been removed from further analysis by their quality control criteria [7].…”
Section: Immunochip In Other Autoimmune Diseasesmentioning
confidence: 56%
“…Only in some exceptions have associations been seen to rare or low frequency variants (in CeD, IBD, PBC and RA), and these are often related to the number of samples analyzed and hence the study's power or methodology (e.g. the use of sequences instead of genotypes) [26]. Two examples serve to demonstrate the complex analysis leading to the discovery of rare variants.…”
Section: Immunochip In Other Autoimmune Diseasesmentioning
confidence: 98%
“…Results of this study indicate that the proportion of heritability because of rare variants was negligible. 126 A recent study performed by crossing >2 strains of yeast in which the traits are known produced an interesting and relevant finding. They were able to account for 100% of the expected heritability through primarily common risk variants each exhibiting only minimal risk effects with gene-to-gene interactions varying from 0% to 50% of the effect.…”
Section: So-called Missing Heritability Phenomenonmentioning
confidence: 99%
“…Moreover, the gene variants identified have modest-effect size and it has been hypothesized that rare variants with bigger effect may explain this "missing heritability" (Manolio et al 2009). However, a recent study, which has resequenced 25 genes from 20 GWAS-identified risk loci overlapping between six common autoimmune disease including psoriasis, has shown that rare variants at known loci have a negligible role in common immune-mediated disease susceptibility, suggesting that the missing heritability likely results from the coexistence of many common variants of weak effect (Hunt et al 2013).…”
Section: Psoriasis Susceptibility Genes Identified By Gwassmentioning
confidence: 99%